2005
DOI: 10.1104/pp.105.064238
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin Synthesis and Expression of Genes Encoding Leucoanthocyanidin Reductase and Anthocyanidin Reductase in Developing Grape Berries and Grapevine Leaves

Abstract: Proanthocyanidins (PAs), also called condensed tannins, can protect plants against herbivores and are important quality components of many fruits. Two enzymes, leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR), can produce the flavan-3-ol monomers required for formation of PA polymers. We isolated and functionally characterized genes encoding both enzymes from grapevine (Vitis vinifera L. cv Shiraz). ANR was encoded by a single gene, but we found two highly related genes encoding LAR. We mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
510
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(566 citation statements)
references
References 39 publications
39
510
3
3
Order By: Relevance
“…The limitation of PA gene expression to young blueberry fruit is reminiscent of the pattern in grape, although in that system, VvANR and VvLAR gene expression is high in seeds and skin until just after ripening initiation (véraison; Bogs et al, 2005). Interestingly, in grape seeds, there is a dramatic spike in VvF3#H, VvDFR, and VvLAR2 expression at ripening initiation, while VvANR and VvANS are also expressed at high levels (Bogs et al, 2005.…”
Section: Pa Synthesis Is Developmentally and Spatially Delimited In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of PA gene expression to young blueberry fruit is reminiscent of the pattern in grape, although in that system, VvANR and VvLAR gene expression is high in seeds and skin until just after ripening initiation (véraison; Bogs et al, 2005). Interestingly, in grape seeds, there is a dramatic spike in VvF3#H, VvDFR, and VvLAR2 expression at ripening initiation, while VvANR and VvANS are also expressed at high levels (Bogs et al, 2005.…”
Section: Pa Synthesis Is Developmentally and Spatially Delimited In Bmentioning
confidence: 99%
“…Interestingly, in grape seeds, there is a dramatic spike in VvF3#H, VvDFR, and VvLAR2 expression at ripening initiation, while VvANR and VvANS are also expressed at high levels (Bogs et al, 2005. It has been suggested that this might correspond to a burst in flavan-3-ol monomer synthesis in seeds (Downey et al, 2003;Bogs et al, 2007).…”
Section: Pa Synthesis Is Developmentally and Spatially Delimited In Bmentioning
confidence: 99%
“…Anthocyanidin is produced from leucoanthocyanidin by LDOX and is also a precursor of anthocyanin and its derivatives. In grape (Vitis vinifera), tissue and temporalspecific regulation of ANR and LAR genes strongly influences PA accumulation and composition during berry development (Bogs et al, 2005). The ANR cluster MD013330 was strongly represented in GoldRush but absent in Royal Gala in libraries derived from young fruit tissues.…”
Section: Cultivar Comparisonmentioning
confidence: 99%
“…Thermal cycling conditions were 95°C for 10 min followed by 40 cycles of 95°C for 30 s, 56°C for 30 s, and 60°C for 60 s. Both cDNA dilutions were run in duplicate. Gene transcripts were normalized to VvUbiquitin1 (TC32075; The Institute for Genomic Research database) by comparing the cycle threshold of the target gene with that of VvUbiquitin1 (Bogs et al, 2005). Gene expression was expressed as mean and SE calculated over all biological replicates.…”
Section: Aquaporin Gene Expressionmentioning
confidence: 99%